Instruments to Assess Depressive Symptoms and Spiritual Distress Investigate Different Dimensions. Issue 2 (14th March 2016) - Bornet, Marc-Antoine; Rochat, Etienne; Dürst, Anne-Véronique; Fustinoni, Sarah; Büla, Christophe; von Gunten, Armin; Monod, Stéfanie
ABSTARCT: Objective : Although affective and spiritual states may share some common clinical features, the precise nature of the relationship between depression and spirituality is still unclear. We tested the hypothesis that two instruments that measure depressive symptoms and spiritual distress describe similar dimensions. Methods : Patients admitted to geriatric rehabilitation (N = 185; mean age 81.3 ± 6.9 years) had depressive symptoms assessed with the 15-item Geriatric Depression Scale (GDS-15) and spiritual distress evaluated with the Spiritual Distress Assessment Tool (SDAT). Results : A principal components analysis pooling GDS-15 and SDAT resulted in a 6-factor solution, with only one factor shared by both dimensions. Conclusions : Depressive symptoms and spiritual distress measured by the two instruments appeared only moderately correlated and corresponded to distinct dimensions.